(3fXe GdJUQja GdYRjs - (3CMeO GdfSais; (3GdRfLGfj , YHO GdhgGH Hf EHQGgje Hf YHO GdhgGH GdNRQLj, YRGdOjf CHh GdaVGFd,J (B655 (3g` s ((3eMeO Hf bGSe GdchOi GdMfai s)
(3ChdgG (B:s
(3hHYO aGdUQa dcd Yde Ce dCgdjI CLd bSe cGf JCdja GdEeGe ajg eUhfG ef Nai GddZR s
(3BNQgG (B:s
(3Ke Ydi CUMGHg hBdg eG GTJGb s
(3JHUQI GdYfhGf (B:s
(3fXes
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B179 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B6 - (3U (B216s
(3eUOQ GbJfGA GdCUd (B:s
(3GdXGgQjI (B(9304) s
Keywords: (3GdUQas